Observation of D±s/D0 enhancement in Au + Au collisions at √sNN=200 GeV - Adam, Jaroslav; Deppner, Ingo Martin; Herrmann, Norbert; Weidenkaff, Philipp (Physical review letters, 2021)
We report on the first measurement of charm-strange meson D-s(+/-) production at midrapidity in Au + Au collisions at root s(NN) = 200 GeV from the STAR experiment. The yield ratio between strange (D-s(+/-)) and nonstrange (D-0) open-charm mesons is presented and compared to model calculations. A significant enhancement, relative to a PYTHIA simulation of p + p collisions, is observed in the D-s(+/-)/D-0 yield ratio in Au + Au collisions over a large range of collision centralities. Model calculations incorporating abundant strange-quark production in the quark-gluon plasma and coalescence hadronization qualitatively reproduce the data. The transverse-momentum integrated yield ratio of D-s(+/-)/D-0 at midrapidity is consistent with a prediction from a statistical hadronization model with the parameters constrained by the yields of light and strange hadrons measured at the same collision energy. These results suggest that the coalescence of charm quarks with strange quarks in the quark-gluon plasma plays an important role in D-s(+/-)-meson production in heavy-ion collisions.
Im Titel ist der Ausdruck"+-" hochgestellt, dabei steht das "-" unter dem "+", das "s" ist tiefgestellt, bei D0 ist die "0" hochgestellt
Im Titel ist "NN" nach s tiefgestellt, der ganze Ausdruck "s NN" steht unter dem Wurzelsymbol
Gesehen am 27.01.2022